2019
DOI: 10.1103/physrevb.100.081403
|View full text |Cite
|
Sign up to set email alerts
|

Quantum thermoelectrics based on two-dimensional semi-Dirac materials

Abstract: We show that a gap parameter can fully describe the merging of Dirac cones in semi-Dirac materials from K-and K -points into the common M -point in the Brillouin zone. We predict that the gap parameter manifests itself by enhancing the thermoelectric figure of merit zT as the chemical potential crosses the gap followed by a sign change in the Seebeck coefficient around the same point. Subsequently, we show that there is also a trade-off feature between the maximum power delivered and the efficiency when the ch… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 37 publications
0
20
0
Order By: Relevance
“…[41]. The theoretical model used in this paper can be extended to other two-dimensional (2D) Dirac materials [44,45] as well. We obtain the AGF in the diffusive regime using the conductivity model developed by Peres et al [46].…”
Section: Introductionmentioning
confidence: 99%
“…[41]. The theoretical model used in this paper can be extended to other two-dimensional (2D) Dirac materials [44,45] as well. We obtain the AGF in the diffusive regime using the conductivity model developed by Peres et al [46].…”
Section: Introductionmentioning
confidence: 99%
“…Appendix A: Derivation of the BdG Hamiltonian Physically, the semi-Dirac dispersion can be realized in a graphene-like systems with breaking the hexagonal symmetry [7,17,20]. Thus we take an artificial honeycomb lattice model with anisotropic nearest-neighbor (NN) hopping as a prototype.…”
Section: Ns Junction Extending Along the X -Axismentioning
confidence: 99%
“…Unlike most Dirac materials that possess liner dispersions in all momentum-space directions [3][4][5], in SDMs the low-energy excitations disperse quadratically in one direction but linearly along the orthogonal direction [6][7][8][9][10]. The unique band structures of SDMs are responsible for a series of novel phenomena [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24], including the consequences of anisotropic aspect in the superconducting order parameter correlations [25][26][27]. Recent theoretical efforts have demonstrated that the superconductivity in SDMs can be induced by arbitrarily weak attractions in the present of random chemical potential [25].…”
Section: Introductionmentioning
confidence: 99%
“…Since the type-III is the critical point between the type-I and the type-II, one may have the following question: Can we understand the behavior of the type-III Dirac cones by taking the limit from the type-I or type-II? So far, electric and thermoelectric transports for tilted Dirac fermions, both the longitudinal and transverse ones, have been intensively studied [34][35][36][37][38][39]. However, previous works are mostly on continuous models, and the study on lattice models is limited.…”
Section: Introductionmentioning
confidence: 99%